Fatores associados à susceptibilidade aos vírus das hepatites A e B entre homens que fazem sexo com homens usuários de profilaxia pré-exposição ao HIV no Rio Grande do Norte - Vechi, Hareton Teixeira (2024)
Men who have sex with men (MSM) are disproportionately more affected by hepatitis A and B virus infections (HAV and HBV infections, respectively), and sexual practices have been implicated as important modes of transmission in this population. According to recommendations from the Brazilian Ministry of Health, every individual on HIV preexposure prophylaxis (HIV PrEP), of which 80-90% are MSM, should undergo assessment of the immune status for HAV and HBV by serological tests to make clinical decisions, addressing individual and collective issues relating to the control and prevention of these infections. This study aims to evaluate the prevalence and factors associated with susceptibility to HAV and HBV among MSM on HIV PrEP in State of Rio Grande do Norte, Northeastern Brazil. It is a cross-sectional study conducted between September 2021 and June 2023, in which participants underwent structured interviews to collect sociodemographic and clinical information. Blood samples were also collected for screening for sexually transmitted infections (STI) and serological testing for HAV and HBV. A total of 287 MSM were enrolled into the study. HAV susceptibility was found in 106 out of 282 (37.6%) participants. Factors associated with HAV susceptibility were: age < 30 years (prevalence ratio [PR]: 2.02; 95% confidence interval [95% CI]: 1.61-2.53), having health insurance (PR: 1.39; 95% CI: 1.19-1.64), sex only with cis men (PR: 1.52; 95% CI: 1.23-1.89), non-steady sexual partner (PR: 1.20; 95% CI: 1.01-1.43), and no lifetime history of STI (PR: 1.25; 95% CI: 1.03-1.53). HBV Susceptibility was found in 58 out of 286 (20.3%) individuals. HBV Susceptibility was significantly associated with: monthly income ≤ 5 minimum wages (PR: 2.02; 95% CI: 1.01-4.05), not having complete vaccination against hepatitis B (PR: 4.52; CI 95%: 2.89-7.06), initiation of HIV PrEP (PR: 2.18; 95% CI: 1.21-3.94), six-month duration of HIV PrEP (PR: 2.16; CI 95%: 1.19-3.91), absence of tattoos (PR: 1.55; 95% CI: 1.00-2.40), and absence of a medical history of STI (PR: 1.65; 95% CI: 1.07-2.54). A significant proportion of susceptibility to HAV and HBV is observed among MSM using HIV PrEP in State of Rio Grande do Norte. Socioeconomic factors, vaccination status, and sexual health issues play critical roles in determining this susceptibility. The integration of screening and vaccination for hepatitis A and B into HIV PrEP services is essential to identify and address the susceptibility issue. Interventions that increase vaccination coverage and promote safer sexual practices are fundamental to mitigate the burden of these infections in this population.